Fuzzy clustering for genetic algorithm based optimized ellipse data in classifying face emotion - Muthukaruppan, Karthigayan; Mohd Rizon, Mohamed Juhari; Sazali, Yaacob; Ramachandran, Nagarajan; Masanori, Sugisaka; Mohd Rozailan, Mamat (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org